A Portrait of State-of-the-Art Research at the Technical University of Lisbon - Seabra Pereira, Manuel (Springer Netherlands : Imprint: Springer, 2007)
The Technical University of Lisbon (UTL) is celebrating this year its 75th anniversary. Being a jubilee occasion, a full program of events took place, including a two-day Symposium on the research at UTL. This Symposium addressed the state-of-art in major areas of excellence at UTL. Science, technology and innovation and the way universities and society in general, create, use and disseminate knowledge have gained a growing signi?cance over the last decades. UTL no doubt embeds a relevant potential of excellence in different areas of research in basic and applied sciences, which bears its development on the basis of a "research university" model. This book contains the edited version of the invited lectures that were delivered by prominent researchers at UTL. This book brings together in a review manner a comprehensive summary of high quality research contri- tions across basic and applied sciences. The contributing papers are organized around the following major areas: - Emergent areas (Nanosciences, Quantic Computations and Infor- tion, Risk and Volatility in Financial Markets); - Basic Sciences (Mathematics, Physics, Chemistry and Materials); - Social Sciences, Economics and Management Sciences; - Life Sciences and Biotechnology; - Engineering and Technologies - Nature, Environment and Sustainability; - Public Health, Food Quality and Safety; - Health and Sport Sciences; - Urbanism, Transports, Architecture, Arts and Design. The transdisciplinary nature of most areas aims to stress a compelling sense of purpose in the work developed.